2015
DOI: 10.1007/s00221-015-4445-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining links between anxiety, reinvestment and walking when talking by older adults during adaptive gait

Abstract: Falls by older adults often result in reduced quality of life and debilitating fear of further falls. Stopping walking when talking (SWWT) is a significant predictor of future falls by older adults and is thought to reflect age-related increases in attentional demands of walking. We examine whether SWWT is associated with use of explicit movement cues during locomotion, and evaluate if conscious control (i.e. movement specific reinvestment) is causally linked to fall-related anxiety during a complex walking ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 48 publications
8
45
0
Order By: Relevance
“…The experimental set up described below is highly comparable to that previously used by Young and colleagues [37]. Participants walked at a comfortable pace over a 6 by 5 grid of 19 black and 11 white wooden blocks (stepping surface of each block = 40cm x 40cm, height of each block = 30cm, total length of the walking path = 4.4m).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental set up described below is highly comparable to that previously used by Young and colleagues [37]. Participants walked at a comfortable pace over a 6 by 5 grid of 19 black and 11 white wooden blocks (stepping surface of each block = 40cm x 40cm, height of each block = 30cm, total length of the walking path = 4.4m).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to disrupting the automaticity of motor performance, researchers have indicated that reinvestment can influence the allocation of attention during gait. Much in the same way as performing a cognitive dual-task while walking can reduce an individual's ability to perceive environmental cues [34,35], researchers have demonstrated that conscious monitoring and control of movement may similarly impair the perception of external information during locomotion [36,37]. Masters and colleagues [33] argued that cognitive resources are required to consciously attend to the process of moving.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blyth et al [21] studied older men and found a strong association between pain and worries about health and overall anxiety status, independently of comorbid depression. There is also evidence of an association between anxiety and falls among older adults [22]. In contrast, a study of cancer patients and their risk of depression and anxiety showed that older adults (over 60 years) with a cancer history had a decreased risk for anxiety and depressive disorders compared to younger adults with cancer [23].…”
Section: Introductionmentioning
confidence: 99%